Effects of 25-hydroxyvitamin D3 on cell growth and cell death via regulation of the vitamin D metabolising system in a cervical adenocarcinoma cell line - Punchoo, Rivak (University of Pretoria, 2023)
Dissertation (MSc (Chemical Pathology)) - University of Pretoria, 2023.